2016
DOI: 10.1002/ird.2042
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Framework to Assess Water Quality for Irrigation and Drainage Canals

Abstract: The rapid pace of economic growth in Egypt has been accompanied by resource depletion and environmental degradation. Consequently, management action and regular assessment to meet the challenges are essential. The aim of this work is to introduce a statistical framework to assess water quality for irrigation and drainage canals in accordance to monitoring objectives that deal with pollutant concentrations and loads. The water quality/quantity data collected from 2000 to 2013 for the El‐Salam Canal and the Hadu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…-Sawy et al,(2015) studied the chemical properties of Bahr Hadus Drain water to evaluate the water quality. The pH ,EC ,SAR , Cd ,Ni and Pb values were (7.92), (1.59 dS.m -1 ), (5.45 mg.L -1 ) ,(0.012 mg.L -1 ) , (0.037 mg.L -1 ) and ( 0.616 mg.L -1 ), respectively , whereas, Shaban (2017) found that BOD values were (106 mg.L -1 ) on Bahr Hadus drain within the maximum limits for water irrigation according to Egyptian Law No.48 ( 1982) El-Samet (2013) carried out a study on Meraga drain located in EL-Gamalia district, Dakahlia Governorate to evaluate drainage water quality. Water samples were seasonally collected from 6 sites along this drain.…”
Section: Introductionmentioning
confidence: 92%
“…-Sawy et al,(2015) studied the chemical properties of Bahr Hadus Drain water to evaluate the water quality. The pH ,EC ,SAR , Cd ,Ni and Pb values were (7.92), (1.59 dS.m -1 ), (5.45 mg.L -1 ) ,(0.012 mg.L -1 ) , (0.037 mg.L -1 ) and ( 0.616 mg.L -1 ), respectively , whereas, Shaban (2017) found that BOD values were (106 mg.L -1 ) on Bahr Hadus drain within the maximum limits for water irrigation according to Egyptian Law No.48 ( 1982) El-Samet (2013) carried out a study on Meraga drain located in EL-Gamalia district, Dakahlia Governorate to evaluate drainage water quality. Water samples were seasonally collected from 6 sites along this drain.…”
Section: Introductionmentioning
confidence: 92%
“…Most of this load comes from agricultural sources, and some from minor sources like domestic and industrial sewage [9]. Nowadays Bahr El-Baqar drain started to receive the biggest amount of wastewater (about 3 BCM every year), while Bahr Hadus receives a wastewater load of about 1.75 BCM every year [10].…”
Section: Introductionmentioning
confidence: 99%
“… M. Shaban et al (2010) carried a research that relied on a tool to design a framework for cost-effective pollution control measures, where GIS support decision support systems "DSS" for water quality management.  Shaban (2017) assembled data collected for the period 2000-2013 for El-Salam Canal and achieved a percentile analysis to facilitate better handling of data.  Ahmed Habash et al (2018) Tailor-made protocol for assessing water quality of irrigation canals: Case study of El Nubaria canals, Egypt.…”
Section: Introductionmentioning
confidence: 99%